Consumer Brand Relationships: Overcoming Its Conceptual Challenges and Development of Propositions - Noor Hasmini Abd Ghani; Md Kashedul Wahab Tuhin (International Journal of Supply Chain Management, 2018)
A stream of branding researchers considered brands as an active partner of human and this concept is challenged by another group as a brand is an inanimate object. In normal phenomenon, the relationship is formed between two people. The purpose of this paper is to overcome this challenge raised by the critics about a brand as a relationship partner of consumer and to develop the proposition regarding consumer brand relationship to establish common consensus about the relationship from between consumer and brand. This paper critically evaluates the literature about consumer brand relationship from the 1980s and onwards consistent with interpersonal relationship literature. This study explores facets of consumer brand relationship to establish the concept and develop six propositions from relationship context. The first it establishes a brand as a human entity. The second it investigates how brand act as a relationship partner. The third it explores the relationship norms that guide the relationship between consumers and brands. The fourth types of relationships consumers maintain with brands. The fifth it also shows high brand equity is the outcome of strong consumer brand relationship. Lastly, it explores strong loyalty resulted from strong consumer brand relationship. There is a scarcity of consumer brand relationship research that integrates different aspect of the concepts, on which the concept stands, developed by the researchers. This study, therefore, integrates different aspect of consumer brand relationship research and establishes the common notions of consumer brand relationship perspective to overcome its conceptual challenge. There is dearth of research that highlights brand supply chain or brand value delivery strategies from consumer brand relationship perspective on which this gives indication of its basis.